2011
DOI: 10.1103/physreve.84.031906
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface hydrophobicity on the conformational changes of polypeptides of different length

Abstract: We studied the effects of surface hydrophobicity on the conformational changes of different length polypeptides by calculating the free energy difference between peptide structures using the bias-potential Monte Carlo technique and the probability ratio method. It was found that the hydrophobic surface plays an important role in the stability of secondary structures of the polypeptides with hydrophobic side chains. For short GAAAAG peptides, the hydrophobic surface destabilizes the α helix but stabilizes the β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…This preference in the gas phase for short polyalanines is not inconsistent with earlier results of others. , It is also in line with the work of Park and Goddard, who showed that polyalanine α-helixes are stabilized by dipole–dipole interaction energy that increases with the number of residues. This result is corroborated by other studies that show α-helical global minima for long polyalanines. More recently, studies of polyalanine and polyalanine derivatives adsorbing on solid surfaces have indicated the formation of α-helixes through simulation (via a course-grained Monte Carlo study) and both α-helixes , and 3 10 -helixes through experiment (via synthesis of self-assembled monolayers), although it must be noted that none of these studies precisely replicate the system studied here. The second difference between the results obtained here and those of Mijajlovic and Biggs is the absolute values of the switching energies: they are significantly higher and lower for 3 10 → 2 7 and α → 3 10 switches, respectively.…”
Section: Results and Discussionsupporting
confidence: 86%
“…This preference in the gas phase for short polyalanines is not inconsistent with earlier results of others. , It is also in line with the work of Park and Goddard, who showed that polyalanine α-helixes are stabilized by dipole–dipole interaction energy that increases with the number of residues. This result is corroborated by other studies that show α-helical global minima for long polyalanines. More recently, studies of polyalanine and polyalanine derivatives adsorbing on solid surfaces have indicated the formation of α-helixes through simulation (via a course-grained Monte Carlo study) and both α-helixes , and 3 10 -helixes through experiment (via synthesis of self-assembled monolayers), although it must be noted that none of these studies precisely replicate the system studied here. The second difference between the results obtained here and those of Mijajlovic and Biggs is the absolute values of the switching energies: they are significantly higher and lower for 3 10 → 2 7 and α → 3 10 switches, respectively.…”
Section: Results and Discussionsupporting
confidence: 86%
“…This should facilitate protein adhesion, and, more importantly, RGD itself can interact with the receptors on the cell membrane to enhance cell adhesion, thus resulting in further enhanced cell adhesion. 51, 52 It was found that the difference of cell attachment on RGD-PTFE and R/H-PTFE was not statistically significant, indicating that the addition of heparin did not further improve cell attachment. Thus, RGD may have played the major role in facilitating cell attachment.…”
Section: Resultsmentioning
confidence: 96%
“…Computer simulation provides a powerful tool of studying adsorption and aggregation of polypeptides onto various substrate surfaces at the atomic level. However, due to the complicated nature of molecular interactions and long time scale involved, the majority of simulation studies merely focused on adsorption behavior and conformational transition of a single polypeptide on surfaces and membranes [15][16][17][18][19][20][21][22]. Only a few simulation studies focused on the influences of surface characteristics on peptide aggregations [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the simplicity and hydrophobicity of its side chains, poly(A) has been a popular model peptide in both computational [22,[26][27][28][29][30] and experimental [31][32][33][34][35][36] studies on peptide aggregation. Very recently, Bernacki and Murphy synthesized poly(A) peptides with different chain lengths (A7 to A25) and investigated the length-dependent aggregation properties of uninterrupted poly(A) peptides in aqueous solutions [36].…”
Section: Introductionmentioning
confidence: 99%